Optimization of ginger (Zingiber officinale) and cinnamon (Cinnamomum verum) on total phenolics, antioxidant activity and loaf volume of bread - Az Zahra Nur An Shilbi; Erni Sofia Murtini (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
As human awareness increases with healthy consumption patterns, food products can be developed into functional foods, one of which is white bread with the addition of ginger and cinnamon. Ginger and cinnamon have phenolic compounds that act as an antioxidant, but the addition in white bread affect the physicochemical and rheological properties of the dough and the loaf volume of white bread. This study aimed to determine the optimum concentration of ginger and cinnamon to produce white bread with the highest total phenol, antioxidant activity, and loaf volume. The research was established with the Response Surface Methodology method using Central Composite Design withtwo factors: concentration of ginger and cinnamon. Minimum and maximum concentrations used for ginger and cinnamon were 1-3% (flour-based) and 2-4% (flour-based), respectively. The optimum result obtained from the program was ginger and cinnamon, at concentration approximately 2.68% and 4% (flour-based), with total phenolic content of 47.90 mgGAE/100g, antioxidant activity of 32.30%, and loaf volume of 154.29%. Optimum white bread had lower loaf volume than controlled white bread.